Donor human milk and risk of surgical necrotizing enterocolitis: A meta-analysis. Issue 3 (June 2019) - Silano, Marco; Milani, Gregorio Paolo; Fattore, Giovanni; Agostoni, Carlo
Summary: Background & aim: The prevention of necrotizing enterocolitis (NEC) is a primary goal in the care of preterm and low birth-weight infants. Donor-banked milk (DM)-feeding has been reported to have a protective effect towards NEC with respect to formula-feeding. All the meta-analysis published so far, have been focused on the protective effect of DM on the overall risk of NEC, none of them focused on the risk of the most severe cases on NEC only, that are those requiring surgery. We conducted a meta-analysis of available evidences on the risk of developing surgical cases of NEC in DM-fed preterm and/or low birth weight infants with respect to those formula-fed. Methods: A search for articles published between January 1960 and January 2018 and addressing the association between DM and surgical NEC was conducted via PubMed, Embase and Cochrane database. We included randomized controlled clinical trials, reporting primary data and involving preterm and/or low birth weight infants fed with preterm formula compared to DM, both as sole diet or complementing own mother's milk. Estimates were pooled using random-effects. Study quality was assessed by GRADE score and risk of bias by the Review Manager software tool. Results: Four papers were included in the meta-analysis. DM did not exert a beneficial effect of DM on the risk of preventing surgical NEC with respect to formula (RR: 0.45; 95% CI: 0.19–1.09). Conclusions: This meta-analysis indicates that DM does not exert a clear protective effect, on the surgical cases of NEC with respect to preterm formula. Since DM feeding implies remarkable extra cost for the preparation, storage and delivery of the milk with respect to preterm formula, stronger evidences are required to recommend this type of feeding as a preventive strategy for surgical NEC. Mother's milk, when available, could represents the best choice. PROSPERO registration number: CRD42015020296